Dissociation of C-Reactive Protein Levels from Long-Chain Omega-3 Fatty Acid Status and Antidepressant Response in Adolescents with Major Depressive Disorder: An Open-Label Dose-Ranging Trial - McNamara, Robert K.; Perry, Mary; Sears, Barry (Journal of Nutritional Therapeutics, 2013)
Major depressive disorder (MDD) is associated with long-chain omega-3 (LCn-3) fatty acid deficits and indices of chronic sustained inflammation including elevated C-reactive protein (CRP) levels. The present study combined a case-control analysis and a prospective 10-week open-label fish oil (FO) supplementation trial to investigate the relationships among plasma phospholipid LCn-3 fatty acid levels, plasma CRP concentrations, and depressive symptoms in adolescent MDD patients. Compared with healthy controls (n=20), MDD patients (n=20) exhibited significantly lower EPA+DHA levels (-62%, pÂ£0.0001) and a higher ratio of arachidonic acid (AA) to EPA+DHA (+78%, p=0.0002). CRP concentrations did not differ between controls and MDD patients (0.16 vs. 0.17 mg/dL, p=0.96), and were positively correlated with depression symptom severity scores in MDD patients (r = +0.55, p=0.01). CRP concentrations were positively correlated with BMI in MDD patients (r = +0.63, p=0.005) and controls (r = +0.69, p=0.002). Low-dose (2.4 g/d) and high-dose (15 g/d) FO supplementation significantly increased EPA+DHA levels in MDD patients, but did not significantly alter CRP concentrations. Baseline and baseline-endpoint change in CRP levels were not correlated with baseline-endpoint reductions in depression severity. Together, these data demonstrate that the lower plasma phospholipid LCn-3 fatty acid composition exhibited by adolescent MDD patients is not associated with higher CRP levels, and that increasing LCn-3 fatty acid status reduces depression symptom severity independent of changes in CRP concentrations. Collectively, these data suggest that CRP concentrations are dissociable from LCn-3 fatty acid status and antidepressant response in adolescent MDD patients.